Super Twisting Sliding-Mode Control of Grid-Tied Quasi-Z-Source Inverters Under Distorted Grid Voltage - Bagheri, Farzaneh; Komurcugil, Hasan; Bayhan, Sertac (IEEE, 2021)
A super twisting sliding mode control (STSMC) method is introduced for grid-tied quasi-Z-source inverters (qZSI) operating under distorted grid voltage. This method is capable to alleviate the chattering phenomena in both ac and dc sides of the system concurrently by generating two smooth control inputs for dc and ac sides of the circuit. Applying the STSMC strategy suppresses the chattering to its minimum while preserving the other important features of the sliding mode control method like zero steady-state error, robustness and fast response. Moreover, the ac side capacitor voltage reference is produced by employing a proportional-resonant (PR) controller. An extra term is added into PR controller so as to eliminate the distortions of the grid current under distorted grid voltage. The effectiveness of the proposed method in suppressing the chattering and generating a harmonic free grid current is certified via simulation results using MATLAB/SIMULINK.
30th IEEE International Symposium on Industrial Electronics (ISIE) -- JUN 20-23, 2021 -- Kyoto, JAPAN
Keywords: Grid-tied quasi-Z-source inverter; super-twisting-sliding mode control; distorted grid voltage